THE EFFECT OF LOCAL ORIGINAL REVENUE, GENERAL ALLOCATION FUNDS, SPECIAL ALLOCATION FUNDS AND PROFIT SHARING FUNDS ON REGIONAL EXPENDITURES IN ACEH PROVINCE - Ayu Mahyu; Devi Andriyani (LPPM Universitas Malikussaleh, 2019)
This study aims to determine the effect of local original Revenues, General Allocation Funds, and Profit Sharing Funds on the Regional Expenditures of Regencies/Cities in Aceh Province, Indonesia. This study uses panel data covering 23 Regencies/Cities in the Province of Aceh during 2013-2017. The Method of data analysis is Panel data regression. The results of the study partially indicated that local original revenue, general allocation funds, special allocation funds, and profit sharing funds have a positive and significant effect on the Expenditures of Regencies/cities in Aceh Province. Simultaneously, local original revenues, general allocation funds, special allocation funds, and profit sharing funds have a positive and significant effect on the Expenditures of Regencies/across in Aceh Province.